PENGARUH LIKUIDITAS DAN STRUKTUR ASET TERHADAP STRUKTUR MODAL DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI - Meilani Maradiaponto; Kurniawan Tjakrawala (Jurnal Paradigma Akuntansi, 2023)
The purpose of this study was to examine the effect of liquidity and asset structure on capital structure with profitability as a moderating variable in manufactures listed on the Indonesia Stock Exchange (IDX) with a research period of 2015-2019. This study using purposive sampling method and obtained 175 company data from the financial statements of manufacturing companies in IDX official website. The data processing technique uses multiple regression analysis and moderator regression analysis (MRA)and also uses the SPSS version 17. The results of this study indicate that liquidity andasset have a negative and significant effect on capital structure. Meanwhile,profitability moderate liquidity to capital structure but profitability does not moderate asset structure to capital structure